EVALUATION OF A HOTEL MANAGEMENT TEXTBOOK BASED ON WORLD LANGUAGE STANDARDS - Aniroh, Kun (Jurnal Pendidikan Bahasa dan Sastra, 2014)
The aim of this study is to evaluate, using world language standards 2007,                  a textbook on hotel management and tourism for intermediate to advanced level students. The respondents of this study were two groups: experts and students. The experts include English lecturers at hotel department and  hotel supervisors. The students include hotel and tourism students. The respondent come from 5 (five) higher tourism colleges. The study utilized the questionnaire developed on World Language Standards 2007, consisting of fifty three indicators that follow: content, exercises, communication, cultures, connections, communities and general elements. A continuous scoring procedure was used in which 1 was for the minimum and 4 was the maximum score. The results revealed these points: Of the ten indicators of general elements the highest score from the students the rated score reached 3.17 points of 4. Of the eleven content indicators of the experts the rated score reached 3.37 points and the score reached 3.36 points for the seven indicators of the exercise. The score of the communication consisting of eleven indicators reached 3.23 points, and of the six indicators of cultures the scored reached at 3.52 points. The next is the score of the connection consisting of three indicators reached at 3.63 points, the communities consisting of five indicators the score reached at 3.68 points and the last is general elements consisting of ten indicators the rated score reached 3.36 points.  The findings showed that the score of the all variables were above three meaning that it is considered good. However, the textbook still needed improving if it will be published as a course book as it was suggested by the students and the experts.